Cholinergic circuits integrate neighboring visual signals in a Drosophila motion detection pathway. - Takemura, S.Y.; Karuppudurai, T.; Ting, C.Y.; Lu, Z.; Lee, C.H.; Meinertzhagen, I.A. (Current Biology, 2011)
Detecting motion is a feature of all advanced visual systems [1], nowhere more so than in flying animals, like insects [2, 3]. In flies, an influential autocorrelation model for motion detection, the elementary motion detector circuit (EMD; [4, 5]), compares visual signals from neighboring photoreceptors to derive information on motion direction and velocity. This information is fed by two types of interneuron, L1 and L2, in the first optic neuropile, or lamina, to downstream local motion detectors in columns of the second neuropile, the medulla. Despite receiving carefully matched photoreceptor inputs, L1 and L2 drive distinct, separable pathways responding preferentially to moving "on" and "off" edges, respectively [6, 7]. Our serial electron microscopy (EM) identifies two types of transmedulla (Tm) target neurons, Tm1 and Tm2, that receive apparently matched synaptic inputs from L2. Tm2 neurons also receive inputs from two retinotopically posterior neighboring columns via L4, a third type of lamina neuron. Light microscopy reveals that the connections in these L2/L4/Tm2 circuits are highly determinate. Single-cell transcript profiling suggests that nicotinic acetylcholine receptors mediate transmission within the L2/L4/Tm2 circuits, whereas L1 is apparently glutamatergic. We propose that Tm2 integrates sign-conserving inputs from neighboring columns to mediate the detection of front-to-back motion generated during forward motion.